The use of acupuncture as a complementary treatment for endometriosis: A systematic review - Lima , Ana Luisa Serrano; Luz, Kelly Cristina Suzue Iamaguchi; Sanguino, Gabriel Zanin; Felipin, Larissa Carolina Segantini; Sampaio, Giovana Tófoli; Murrugarra , Lais Kaori Sato; Dias, Giovana Munhoz; Luckner, Ana Clara; Santos , Lorraine de Souza; Santoro, Fernanda Furlan; Carvalho, Rita de Cássia Pereira; Frez , Flávia Cristina Vieira (Seven Editora, 2023)
Endometriosis is a multifactorial estrogen-dependent and inflammatory gynecological condition characterized by the presence of fragments of endometrial tissue outside the uterine cavity. Due to the negative impact on the physical and psychological appearance of women, endometriosis is considered a public health problem. The Ministry of Health presents the National Policy on Integrative and Complementary Practices (PNPIC), which aims to incorporate and implement experiences outside of Traditional Medicine, among which Acupuncture stands out, a Chinese technique that has proven to be effective for treating pain . This work aims to identify evidence-based recommendations in the literature on the use of Acupuncture and its resources for the adjuvant treatment of endometriosis and is a systematic review of the literature using a pre-established protocol for the search, selection and extraction of data. From this review study, it was possible to verify the therapeutic efficacy of acupuncture as a complementary and integrative treatment for endometriosis, as the technique excites receptors and nerve fibers leading to the release of endogenous opioids, resulting in continuous pain relief. Furthermore, studies have shown that the practice of acupuncture provided greater relief from pelvic pain when compared to the use of drug therapy, in addition to improving the quality of life of women affected by this disease. DOI:https://doi.org/10.56238/sevened2023.004-010